Gender Responsive Urban Public Places in Dhaka City: A Planning Perspective - Rashied, Masudur (Journal of Bangladesh Institute of Planners, 2017)
Women are now getting involved in workforce because of their economic freedom and social progress. They now frequently move outside their home and are exposed to the male dominated urban sphere. Historically, cities are only made for men, just like Dhaka, the capital city of Bangladesh. The aim of this study is to find out the gender responsiveness of public places in Dhaka city. To identify the gender responsiveness of urban public places, five major variables were selected namely- design, isolation, lighting, safety, and management. Based on these five variables, this study tried to identify the gender responsiveness of Gulshan and Khilkhet - the two significant representative areas of Dhaka city. In the two study areas, a total of 230 samples were collected by using convenient sampling technique. It was found that planned areas have wide and visible roads, well-lit streets and minimal chances for having entrapment sites, or rather unplanned areas. Moreover, planned areas in many ways facilitate women for their regular movement and help to make cities more responsive and secured. The findings of this study helps understand the importance of gender sensitization and the prospects of urban planning for gender responsiveness as well. JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 117-129